Nutritional evaluation of corn grown using different organic fertilizers for slow-growing broilers - Campos, Carla Fonseca Alves; Siqueira, Jefferson Costa de; Rodrigues, Kênia Ferreira; Vaz, Roberta Gomes Marçal Vieira; Mello, Susana Queiroz Santos; Silva, Gerson Fausto da; Vieira, Danilo Vargas Gonçalves; Parente, Iberê Pereira; Silva, Valquíria Sousa; Araújo, Caroliny Costa (Semina: Ciências Agrárias, 2019)
The aim of this study was to evaluate the chemical composition, energy values and nutrient metabolizability coefficients of corn grown using different organic fertilizers and its use for feeding slow-growing broilers. Two experiments were conducted. In the first experiment, two hundred 21-day-old broilers were distributed in a completely randomized design, with five treatments and four replicates of 10 birds per experimental unit. The treatments were a control diet and four test diets (corn fertilized with crotalaria, corn fertilized with millet, corn fertilized with humus, and corn without fertilization), including corn at 30% in the control diet. The apparent metabolizable energy, apparent metabolizable energy corrected for nitrogen balance, and apparent metabolizability coefficients of dry matter, crude protein and gross energy were determined. In the performance trial, two hundred and fifty 1-day-old chicks were distributed in a completely randomized design into five treatments (T1 - control diet with commercial corn, T2 - corn without fertilization, T3 - corn fertilized with humus, T4 - corn fertilized with millet and T5 - corn fertilized with crotalaria) and five replicates of 10 birds per experimental unit. Weight gain, feed intake, feed conversion and final weight at 20 days were evaluated. The AME and AMEn values of corn fertilized with crotalaria, millet, humus and corn without fertilization were 3246 and 3239 kcal kg?1; 2965 and 2954 kcal kg?1; 2909 and 2877 kcal kg?1; and 3265 and 3201 kcal kg?1, respectively. The apparent metabolizable coefficients of DM, CP and GE were: 89.75%, 66.88% and 88.5% for corn fertilized with crotalaria; 84.38%, 58.73% and 81.4% for corn fertilized with millet; 80.38%, 53.45% and 78.95% for corn fertilized with humus; and 89.48%, 68.95% and 87.85% for corn without fertilization, respectively. Feeding broilers with corn cultivated with different fertilizers affected (P < 0.05) weight gain, feed intake, feed conversion and final weight. The treatments using corn fertilized with crotalaria, millet, humus and commercial corn did not differ, with better results in relation to corn crop cultivated without fertilization. The use of crotalaria and millet as a green manure, and humus derived from dairy manure are alternatives that can be used on corn crop as they resulted in grains with adequate nutritional composition, energy values and metabolizable coefficients for slow-growing broilers from 1 to 20 days of age.